IMPACT OF MICRONUTRIENT DEFICIENCIES ON CHILD DEVELOPMENT - Fatima Martoub Mohsen Abdel Reda; Fatima Qasim is an ignorant Hindu; Muhammad Baqir Abdel Hassan Abdel Zaid; Hawraa Ali Abdul Amir Saleh; Louay Qusay Reda Kazem (Journal of Medical Genetics and Clinical Biology, 2024)
Micronutrient deficiencies pose a significant threat to child development, affecting millions of children globally. This paper explores the critical role of essential vitamins and minerals in the physical, cognitive, and emotional growth of children. It highlights the prevalence and impact of deficiencies in key micronutrients such as iron, vitamin A, iodine, and zinc. The study examines how these deficiencies can lead to severe developmental issues, including impaired cognitive function, stunted growth, and weakened immune systems. By analyzing various case studies and intervention programs, the paper underscores the importance of addressing micronutrient deficiencies through comprehensive public health strategies. It advocates for policy initiatives aimed at improving nutrition education, fortifying foods, and ensuring equitable access to supplements, particularly in low- and middle-income countries. The findings emphasize that mitigating micronutrient deficiencies is crucial for fostering healthy development and unlocking the full potential of children worldwide